The Influence of Deep Learning Approach and Learning Motivation on Science Learning Outcomes of Phase C Elementary School Students in Cluster 1, South Tondano District - Trinny Meifira Kalalo; Widdy H.F. Rorimpandey; Ni Dewi Eka Suwaryaningrat (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study aims to determine the influence of the deep learning approach and learning motivation on science learning outcomes of Phase C elementary school students in Cluster 1, South Tondano District. This research employs a quantitative approach with a causal associative research type. The sample consisted of 112 students selected through purposive sampling and saturated sampling techniques. Data collection was conducted using a survey method with questionnaire instruments. Data analysis utilized simple linear regression and multiple linear regression with SPSS version 25 for Windows. The results showed that: (1) There is a positive and significant influence of the deep learning approach on science learning outcomes of Phase C elementary students by 40.2%, with tcalculated > ttable (8.595 > 1.981); (2) There is a positive and significant influence of learning motivation on science learning outcomes of Phase C elementary students by 53.5%, with tcalculated > ttable (11.244 > 1.981); and (3) There is a positive and significant influence of the deep learning approach and learning motivation together on science learning outcomes of Phase C elementary students by 62.9%, with Fcalculated > Ftable (92.306 > 3.080). In conclusion, the deep learning approach and learning motivation have a positive and significant influence on science learning outcomes of Phase C students in Cluster 1, South Tondano District.Keywords:Deep Learning Approach, Learning Motivation, Learning Outcomes